ISOLASI GELATIN DARI BERBAGAI BAHAN BAKU HEWANI : REVIEW JURNAL - Devia Setyaningsih; Kokom Gunawan; Melisa Puspitasari; Nieda Berliana Eiko; Neni Sri Gunarti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Indonesia is a country that is rich in a variety of natural resources, one of which is animal. Therefore, the isolation of gelatin from various other types of animals began to be developed. Gelatin is the result of the decomposition of animal protein which has found many functions in both the food and pharmaceutical fields. Gelatin is used as a stabilizer, gelling agent, binder, thickener, and emulsifier. The method used is to search for research journal literature through electronic databases such as Google Schoolar and Sciene Direct. The results of several studies show that gelatin has water content, ash content, protein content and fat content with several different animal raw materials.